Analysis of the Influence of Bank Loans on the Financial Performance of the Supermase Gold Shop in Karang Jati - Fitriyani, Nofi; Maryani, Tri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the management of bank loans at Superman Gold Store and its impact on the financial performance of the business. This study focuses on how the use of bank loans can improve the operational capacity and profitability of the store amidst the challenges of gold price fluctuations and interest expenses. This study is based on the theory of financial management and operational strategy. The research methods used include interviews with store managers and analysis of financial statements, which are analyzed qualitatively to evaluate the impact of loans on key financial indicators. The results of the study indicate that bank loans contribute positively to an increase in net income by 40% and net profit by 50%. In addition, the store's liquidity ratio increased from 1.2 to 1.8, although the solvency ratio also increased from 0.4 to 0.6. The main obstacles in managing loans are gold price fluctuations and high interest expenses. To overcome these challenges, the store implemented mitigation strategies such as strict cash flow management, installment payment priorities, and active monitoring of market prices. However, the effectiveness of these strategies still requires further evaluation. This study has limitations in terms of time coverage and external factors that can affect the results. These findings provide insight for similar business actors in optimizing the use of bank loans to support business growth and financial stability.